2010
DOI: 10.1093/ndt/gfq104
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein induces hypertrophy in podocytes via TGF- 1 and p27Kip1: implications for diabetic nephropathy

Abstract: PTHrP seems to participate in the hypertrophic signalling triggered by HG. In this condition, AngII induces the upregulation of PTHrP, which might induce the expression of TGF-beta(1) and p27(Kip1). These findings provide new insights into the protective effects of AngII antagonists in DN, opening new paths for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 31 publications
3
50
0
1
Order By: Relevance
“…Although the STZ model has limitations for assessing long-term histomorphological changes in the diabetic kidney (Gross et al, 2004); our findings might have pathophysiological implications since the amount of proteinuria is a reliable predictor of diabetic nephropathy (D'Amico & Bazzi, 2003;Hirschberg, 1996). In a more recent study, Romero et al (2010) observed that PTHrP plays a key role in the mechanisms of HG-induced podocyte hypertrophy. In these studies, HG-induced podocyte hypertrophy was inhibited by the presence of a specific PTHrP neutralizing antibody.…”
Section: Pthrp In Chronic Renal Injury: Diabetic Nephropathy (Dn)mentioning
confidence: 72%
See 4 more Smart Citations
“…Although the STZ model has limitations for assessing long-term histomorphological changes in the diabetic kidney (Gross et al, 2004); our findings might have pathophysiological implications since the amount of proteinuria is a reliable predictor of diabetic nephropathy (D'Amico & Bazzi, 2003;Hirschberg, 1996). In a more recent study, Romero et al (2010) observed that PTHrP plays a key role in the mechanisms of HG-induced podocyte hypertrophy. In these studies, HG-induced podocyte hypertrophy was inhibited by the presence of a specific PTHrP neutralizing antibody.…”
Section: Pthrp In Chronic Renal Injury: Diabetic Nephropathy (Dn)mentioning
confidence: 72%
“…In this way, while PTHrP (1-36) was shown to stimulate cyclin D 1, thus promoting podocytes to enter into G 1 , it also downregulates cyclin E, hence blocking the cell cycle later in G 1 . Moreover, PTHrP is able to upregulate the negative cell cycle regulatory protein p27 Kip1 which plays a key role in diabetic cell hypertrophy by preventing activation of cyclin E activity and arresting the cell cycle later in G 1 (Huang & Preisig, 2000;Romero et al, 2010). Interestingly, Romero et al (2010) found that the pharmacological blockade of the PTH1R inhibited the p27 Kip1 upregulation induced by both HG and AngII.…”
Section: Pthrp In Chronic Renal Injury: Diabetic Nephropathy (Dn)mentioning
confidence: 99%
See 3 more Smart Citations